A Chemical Synthesis of Benzo[a]pyrene Hapten and Its Application in a Streptavidin-Horseradish Peroxidase-Based Enzyme-Linked Immunological Analysis. (4th February 2018) - Ma, Zhen; Zhuang, Huisheng
Abstract : A specific BaP hapten was synthesized and BaP antigens (immunogen, coating antigen) were prepared using diverse methods. Based on these works, a streptavidin-horseradish peroxidase-based enzyme-linked immunological analysis was developed and firstly used to detect BaP. Several physiochemical factors that may influence the assay performance were optimized in the assay. Under optimal conditions, a detection limit of 0.0094 ng mL −1 was obtained and good linearity was achieved within a range of 0.03–35.40 ng mL −1 . Satisfactory recovery of spiked samples (91.12–109.23%) was obtained and the coefficient of variation was acceptable. Finally, the detection results of BaP in environmental and food samples were consistent with those obtained using high-performance liquid chromatography. The proposed immunoassay is reliable and has great potential for detecting trace amounts of BaP.